2012
DOI: 10.1111/jfq.12011
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Physicochemical Behavior of Soursop Fruits Refrigerated with 1‐Methylcyclopropene

Abstract: The effect of 1-methylcyclopropene (1-MCP) on the ripening of a native variety of soursop (Annona muricata L.) under refrigerated storage was evaluated. Control fruits were stored at 25 and 16C, and a group of fruits was exposed to 200 or 400 nL/L of 1-MCP and then stored at 16C. The effect of 1-MCP on soursop fruits stored at 16C (6 days) and then at 25C was also studied. Fruits stored at 25C ripened after 4-6 days. Fruits held at 16C ripened after 8-9 days; however, chilling injury symptoms were observed. 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
(28 reference statements)
1
20
0
6
Order By: Relevance
“…Annona muricata L ., commonly known as soursop, has received considerable attention from the public because numerous studies have been conducted and indicated that soursop fruit is nutritionally high in carbohydrates and contains appreciable amounts of micronutrients and minerals (Agu & Okolie, ; de Souza, Pereira, Queiroz, Borges, & de Deus Souza Carneiro, ). However, one of the apparent features of this fruit is that it softens and bruises easily, and releases an unpleasant strong smell when ripe (Espinosa, Ortiz, Tovar, Mata, & Montalvo, ). This might be due to the soursop fruit exhibiting double sigmoidal growth kinetics that comprises an initial phase and a final phase of rapid growth (Worrell, Sean Carrington, & Huber, ) with high respiration rate (Lam & Zaipun, ).…”
Section: Introductionmentioning
confidence: 99%
“…Annona muricata L ., commonly known as soursop, has received considerable attention from the public because numerous studies have been conducted and indicated that soursop fruit is nutritionally high in carbohydrates and contains appreciable amounts of micronutrients and minerals (Agu & Okolie, ; de Souza, Pereira, Queiroz, Borges, & de Deus Souza Carneiro, ). However, one of the apparent features of this fruit is that it softens and bruises easily, and releases an unpleasant strong smell when ripe (Espinosa, Ortiz, Tovar, Mata, & Montalvo, ). This might be due to the soursop fruit exhibiting double sigmoidal growth kinetics that comprises an initial phase and a final phase of rapid growth (Worrell, Sean Carrington, & Huber, ) with high respiration rate (Lam & Zaipun, ).…”
Section: Introductionmentioning
confidence: 99%
“…El 100% de los frutos GR y tratados con emulsiones en ambas diluciones almacenados a 16 ºC, desarrollaron síntomas de daño por frío como son: endurecimiento del fruto, pigmentos oscuros en la pulpa y oscurecimiento del eje central (Figura 3); el daño fue mayor al reportado por Espinosa et al (2012) y pudo ser por la variabilidad en el índice de corte.…”
Section: Resultados Y Discusiónunclassified
“…Una tecnología aplicada en la guanábana para conservación en fresco, es la aplicación de 1-metilciclopropeno (1-MCP). Espinosa et al (2012) reportaron que en los frutos de guanábana tratados con 200 y 400 nL L -1 por 24 h y almacenados a 16 ºC, se conservaron por 10 días. Otra metodología empleada para alargar la vida de anaquel de los frutos perecederos, es el uso de emulsiones a base de ceras (CISNEROS; KROCHTA, 2002).…”
Section: Introductionunclassified
“…Tovar-Gómez et al [29] recorded similar results to those obtained in this investigation at 12 days of storage in soursop fruits treated with 1-MCP stored at 13 ± 2°C. Espinosa et al [44] indicate that the increase in TSS can be attributed to the hydrolysis of starch, sucrose, pectins, and other soluble compounds such as organic acids or amino acids. e variation in the TSS can be attributed to the type of fruit; the soursop is classified as a multiple fruit derived from several separate individual flowers, whose fertilized ovaries merge to form a single structure, in which each individual fruit corresponds to a berry [45,46].…”
Section: Total Soluble Solids (Tss)mentioning
confidence: 99%